Immature tooth with the coexistence of dilaceration and radicular dens invaginatus - Niharika Harakabhavi Mutt; Srinivas Nallanchakrava; Devi Rebecca (Journal of Oral Research and Review, 2024)
Trauma to the developing permanent successors leads to alteration in form, size, structure, and quantity of teeth. Management of teeth with such morphological complexity becomes challenging. The severity of the anomaly decides the treatment planning. A case of coexistence of radicular dens invaginatus and dilaceration is reported, which was to be managed surgically due to uneventful endodontic attempts and complicated root anatomy.